MODEL PENGEMBANGAN KURIKULUM MURRAY PRINT DAN LAURIE BRADY DALAM IMPLEMENTASI KURIKULUM MERDEKA DI INDONESIA - Jozuna Aziz Kusuma Mukti; Bachtiar Sjaiful Bachri; Lamijan Hadi Susarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the curriculum development models proposed by Murray Print and Laurie Brady and their relevance to the implementation of the Merdeka Curriculum in Indonesia. Curriculum development is an important component in improving the quality of education because it determines the direction, objectives, learning processes, and evaluation systems used in schools. Murray Print emphasizes a systematic, structured, and continuous evaluation approach in curriculum development, while Laurie Brady focuses on flexibility, teacher creativity, and contextual learning processes. The research method used in this article is a literature study by analyzing books, journals, and official documents related to curriculum development and the Merdeka Curriculum. The results show that the Merdeka Curriculum combines the structured approach of Murray Print with the flexible and interactive approach of Laurie Brady. This combination supports student-centered learning and encourages teachers to become innovative curriculum developers in the classroom. Therefore, the integration of both models is considered relevant for improving the quality of education in Indonesia in the 21st century. Keywords: Curriculum Development, Murray Print, Laurie Brady, Merdeka Curriculum